Calculating vehicle intensiveness increase on eid al-fitr day with anfis method - Pratama, Rendy Bagus; Utami, Ema; Wibowo, Ferry Wahyu (International Journal Artificial Intelligent and Informatics, 2018)
the number of motorized vehicles increases every year, especially private vehicles and is not offset by inadequate access until the road becomes more crowded, even traffic jams occur, especially during public holidays and national holidays. for example, during eid holidays there is a density of traffic flow when going back and forth every year, with the development of current technology the density of traffic flows that occur can be calculated so that it will be easier to anticipate in the future. but in this study only will examine the parameter values that cause the vehicle to occur density and accumulation, because it can be developed with parameter values so that the results can be obtained efficiently in solving traffic density. From the results of the anfis method, efficiency is obtained, namely on h-1 and h days of 2014, and 2017 can use Parameters with magins of 6,3% and 4,32%, while 2015 and 2016 can use parameters with margins 1,79% and 0,79%. and for the h + 1 day of 2014, 2016, and 2017, it is more efficient to use parameters with margins 1,4% and only parameters in 2015 which have the efficiency value using parameters with margin -6,17. anfis application in this calculation can be developed in a prediction system.